2013
DOI: 10.1186/1475-9276-12-46
|View full text |Cite
|
Sign up to set email alerts
|

Health inequalities as a foundation for embodying knowledge within public health teaching: a qualitative study

Abstract: IntroductionRecent UK health policies identified nurses as key contributors to the social justice agenda of reducing health inequalities, on the assumption that all nurses understand and wish to contribute to public health. Following this policy shift, public health content within pre-registration nursing curricula increased. However, public health nurse educators (PHNEs) had various backgrounds, and some had limited formal public health training, or involvement in or understanding of policy required to contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…The approach to service practice allows the process of reflection and learning of various experiences in the context of the service attributing meaning to the information received to interpret them, relating them to their life situations. 7 The theoretical framework that guides the thought of professional formation, which bases this study, shows that this is a process in permanent becoming, not only as an update that occurs from the accumulation of information, but that occurs through contextualized training with reality and that builds knowledge from critical reflection. 8 When considering the thematic relevance of Pedagogical Training, the object of this study is the pedagogical training of teachers performed in the Technical Schools of the Unified Health System.…”
Section: The Actions Of the Network Are Coordinated By The General Comentioning
confidence: 91%
“…The approach to service practice allows the process of reflection and learning of various experiences in the context of the service attributing meaning to the information received to interpret them, relating them to their life situations. 7 The theoretical framework that guides the thought of professional formation, which bases this study, shows that this is a process in permanent becoming, not only as an update that occurs from the accumulation of information, but that occurs through contextualized training with reality and that builds knowledge from critical reflection. 8 When considering the thematic relevance of Pedagogical Training, the object of this study is the pedagogical training of teachers performed in the Technical Schools of the Unified Health System.…”
Section: The Actions Of the Network Are Coordinated By The General Comentioning
confidence: 91%
“…Approaching public health in education presupposes praxis, articulating practice with the theme of public health as a difficult area for dialogue and understanding among students. It is also notable that in most of the studies analyzed in this category there have been report on the unpreparedness of students to address social determinants since their training is only focused on the aspects related to the biomedical models [17,[20][21][22][23]. In addition, some studies indicated that students felt ill-prepared to deal with social and structural factors due to the complexity of the demanded care based on the individual needs of patients.…”
Section: In-service Learningmentioning
confidence: 99%
“…Nursing practice has been highlighted as an action allowing the visibility of health disparities by students, preparing them to adequately address these issues in situations encompassing various inequalities [17,[20][21][22][23]. Inservice learning contributes to the development of various abilities in students to learn from others through active reflection.…”
Section: In-service Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Mabhala 42 identificou no Reino Unido políticas de saúde a partir das quais os profissionais da enfermagem podem contribuir para a redução das inequidades no cotidiano das ações de saúde pública. O conhecimento necessário para incorporar a saúde pública no ensino necessita de uma visão ampla de saúde e refletir e aprender com a experiência e práticas pedagógicas apropriadas.…”
Section: Contexto Atual Das Abordagens Metodológicas E Políticas Paraunclassified